Climate Variability in the Origin Countries a "Push" Factor on Tourist Arrivals in the Philippines - Saverimuttu, V.; Varua, Maria (Routledge, 2014)
The objective of this paper is to test the impact of climate variability in origin countries as a “push factor” on tourist arrivals, specifically in the Philippines, and to select a suitable proxy to measure climate variability. This paper uses the Southern Oscillation Index (SOI) constructed by the Australian Bureau of Meteorology. Climate variability is strongly linked to the El Niño Southern Oscillation (ENSO) and this link is used by meteorologists to forecast changes in weather globally. SOI is a widely used indicator of the ENSO and its best known extremes are the El Niño (warm phase) and La Niña (cold phase) effects. The study proves to some extent that there is a significant increase in US tourist arrivals in the Philippines when La Niña-like weather conditions prevail in the USA. More importantly, the SOI proved to be a good measure of climate variability.